A study of self medication pattern in Punjab - S, Shveta; S, Jagmohan (Indian Journal of Pharmacy Practice)
The objective of this study was to describe and examine the self medication pattern in the state of Punjab. A sample of 300 nuclear families from 5 different districts of Punjab were randomly selected for the study. The study showed that the prevalence of self medication was high in the educated group rather that uneducated group. Self medication was mostly employed for pain, cough, fever, and cold. After analgesic there was priority for food supplements, as 73% of population used to go for self medication of food supplements. Chemists/ Pharmacists were the major source of information for self medication, followed by friends and advertisement. From the study it was concluded that majority of the persons go for self medication without proper knowledge of dose, Adverse drug reactions, Drug interactions. Hence, the issue needs to be addressed by the responsible authorities of State Pharmacy Council/Ministry of Health.
Keywords: Self medication; Punjab